1985
DOI: 10.1002/jso.2930280304
|View full text |Cite
|
Sign up to set email alerts
|

Postirradiation soft tissue sarcoma occurring in breast cancer patients: Report of seven cases and results of combination chemotherapy

Abstract: Seven cases of soft tissue sarcoma developing after primary or postoperative radiotherapy for breast carcinoma are reported. The sarcomas occurred within the irradiated volume, after a latent period of 4-26 years. These cases conform well to established criteria for the diagnosis of radiation-induced sarcoma. Chemotherapy, consisting of the four-drug combination CYVADIC (cyclophosphamide, vincristine, adriamycin, DTIC) was employed in six of the seven patients. Only two of them achieved partial remission, last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 8 publications
0
33
0
Order By: Relevance
“…Our results with chemotherapy confirm that response to such treatment tends to be poor. 9,22,32,65,72,73 Kuten et al 73 reported seven patients with RIS after irradiation for breast carcinoma who were treated with a standard four-drug combination. Only 2 patients achieved partial disease remission, lasting 2 and 3 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results with chemotherapy confirm that response to such treatment tends to be poor. 9,22,32,65,72,73 Kuten et al 73 reported seven patients with RIS after irradiation for breast carcinoma who were treated with a standard four-drug combination. Only 2 patients achieved partial disease remission, lasting 2 and 3 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…All 7 patients died within 6 -36 months of an RIS diagnosis. 73 To our knowledge, treatments using nonconventional methods such as a combination of RT and hyperthermia have not been the subject of extended studies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported poor survival and local recurrence rates even after combining surgery with standard adjuvant chemotherapy [28,85,87,99]. Lagrange et al [82] reported no difference in the survival rate between patients treated with surgery and those treated with surgery plus chemotherapy.…”
Section: Role Of Chemotherapymentioning
confidence: 99%
“…FNA cannot be expected to provide definitive information about the histologic architecture of RIS nor can FNA provide adequate material for an immunohistochemical evaluation. Therefore, core needle or incisional biopsies are preferred: they provide accurate and satisfactory sampling [51, [99] 5c Case reports (n ϭ 2) Case report and literature review Velaj and DeLuca (1987) [4] 5c Radiographic review (n ϭ 1) Case report and literature review Olcina et al (2008) [11] 5c Case report (n ϭ 1) Case report and literature review Chahin et al (2001) [14] 5c Case report (n ϭ 1) Case report and literature review Pendlebury et al (1995) [17] 5c [78] 5c Case report (n ϭ 2) Case report and literature review Kunkel et al (2008) [57] 5c Case report (n ϭ 1) Case report and literature review Quadros et al (2006) [80] 5c Case report (n ϭ 1) Case report and literature review Kuten et al (1985) [87] 5c Case report (n ϭ 7) Case report and literature review Khan et al (2009) [88] 5c Case report (n ϭ 1) Case report and literature review Plotti et al (2006) [91] 5c Case report (n ϭ 1) Case report and literature review Brenin et al (1998) [86] 5c Case report (n ϭ 1) Case report and literature review Feigenberg et al (2002) [100] 5c Case report (n ϭ 3) Case report and literature review Schulz et al (2000) [121] 5c Case report (n ϭ 3) Case report and literature review Givens et al (1999) [122] 5c Clinical review (n ϭ 85) Analysis of prognostic factors for RIS Okuno and Edmonson (1998) [113] 5c Case reports (n ϭ 2) Case report and literature review Mano et al (2006) [102] 5c Case report (n ϭ 1) Case report and literature review Perez-Ruiz et al (2009) …”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation